The Blue Waqf Model Integrating Blue Economy and Productive Waqf for Coastal Empowerment - Faidzin Firdhaus; Ikhtiagung, Ganjar Ndaru; Priyanto, Sasongko Adi; Setyono, Fredi; Pratama, Haikal Firmansah Anas (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2025)
This study aims to formulate and validate the Blue Waqf Model as an innovative framework integrating Islamic social finance with the blue economy to achieve sustainable coastal community empowerment. Employing a qualitative descriptive approach, thirty‑two participants were involved, including waqf administrators, Islamic financial officers, fishermen cooperatives, and local government officials in Central Java. Data were collected through semi‑structured interviews, focus group discussions, and document analysis, and analyzed using thematic content methods to identify key emerging patterns. The results demonstrate that Blue Waqf effectively bridges Islamic philanthropy and marine‑based economic resilience. Three pillars underpin its success: financial innovation through Cash Waqf Linked Blue Sukuk, blockchain‑based digital transparency, and cross‑sectoral collaboration among public, private, and religious institutions. Implementation of the model improved fishermen household income by 24 percent and environmental participation by 37 percent. The study contributes theoretically to the discourse on Islamic sustainable finance and provides an applied framework for faith‑based blue‑economy policy. Its practical implications highlight the importance of collaborative governance and Sharia‑compliant financing mechanisms to support long‑term coastal resilience and sustainability.